2022
DOI: 10.1007/s00062-022-01192-9
|View full text |Cite
|
Sign up to set email alerts
|

Remote Training of Neurointerventions by Audiovisual Streaming

Abstract: Background Remote access of trainees to training centers via video streaming (tele-observership, e‑fellowship) emerges as an alternative to acquire knowledge in endovascular interventions. Situational awareness is a summary term that is also used in surgical procedures for perceiving and understanding the situation and projecting what will happen next. A high situational awareness would serve as prerequisite for meaningful learning success during tele-observerships. We hypothesized that live perc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In a study using online streaming of cases where 6 fellows observed 6 mentors practicing in different high-volume centers in 5 different countries over a 12-month period, the trainees reported high levels of situational awareness with a perceived improvement of their neurointerventional knowledge. 79 Another study using virtual reality simulations demonstrated an enhanced capability of performing endovascular procedures on the virtual reality simulator. 80 Although it remains to be seen whether this translates into enhanced procedural performance in real cases, it is a promising option to extend training in certain regions with few operators with advanced knowledge in other neurointerventional procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using online streaming of cases where 6 fellows observed 6 mentors practicing in different high-volume centers in 5 different countries over a 12-month period, the trainees reported high levels of situational awareness with a perceived improvement of their neurointerventional knowledge. 79 Another study using virtual reality simulations demonstrated an enhanced capability of performing endovascular procedures on the virtual reality simulator. 80 Although it remains to be seen whether this translates into enhanced procedural performance in real cases, it is a promising option to extend training in certain regions with few operators with advanced knowledge in other neurointerventional procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The goal is to expose young neurointerventionalists to the breadth of neurointerventional procedures performed by highly experienced neurointerventional experts. 8 The e-fellowship is a specific use case for live case broadcast that has been a part of neurointerventional education since the beginning of the field. 9 The e-fellowship program is currently being further developed to reach out to other regions, such as Central Asia.…”
Section: New Online Tools To Speed-up Training Of Neurointerventional...mentioning
confidence: 99%